A Firm Bargaining with Many Workers - Andreas Westermark (Uppsala University, Department of Economics, 1998)
The purpose of this paper is to analyze bargaining between a firm and a finite set of workers. In particular employment choice and the payoffs in equilibrium are studied. In the model, the firm first selects the workers it wants to hire. The selected workers then decide whether they want to proceed in bargaining with the firm. Finally, bargaining takes place. In contrast to Stole & Zweibel (1996), we assume that contracts are binding. The payoff for a worker is given by a share of the contribution to production, treating all other workers as employed, in addition to the worker's outside option.
urn:nbn:se:uu:diva-2401
Keywords: C78; D21; J23; 330; bargaining; labor demand